Concise encyclopedia of composite materials - Mortensen, A. (Elsevier, 2007)
This book draws its material from the award-winning Encyclopedia of Materials: Science and Technology, and includes updates and revisions not available in the original set. This customized collection of articles provides a handy reference for materials scientists and engineers with an interest in composite materials made from polymers, metals, ceramics, carbon, biocomposites, nanocomposites, wood, cement, fibers, etc.
Keywords: Composite materials -- Encyclopedias.; elektronické knihy; electronic books